EFFECT OF 12 WEEKS OF RECREATIONAL SOCCER ON BONE MINERAL DENSITY AND SARCOPENIA IN THE ELDERLY: A RANDOMIZED CLINICAL TRIAL - Guilherme Henrique de Lima Matias; André dos Santos Costa; Romulo Maia Carlos Fonseca (Journal of Physical Education, 2022)
ABSTRACT Objective: To verify the effect of recreational soccer on bone mineral density and sarcopenia in the elderly. Methods: Fourteen elderly people aged 65.9 ± 3.4 years were selected. They were separated into two groups: the intervention group and the control group; the intervention group played recreational soccer for 12 weeks on two days of the week. Assessments were performed for bone mineral density and body muscle mass before and after the intervention. For statistical analysis, the repeated measures ANOVA with Bonferroni’s post hoc test was used. Results: After 12 weeks, there was a significant change in bone mineral density in the region of the total femur (p = 0.020). Analyzing the participants’ sarcopenia, no significant results were found after the intervention period. Conclusion: Playing recreational soccer causes a significant improvement in the total femur and maintains bone regions in the spine, whole body, and femoral neck. Also, it promotes a removal from the threshold for sarcopenia screening in the elderly.